FCSIT WAP based student's information system / Norazlina Khamis and Ang Gim Wah - Khamis, Norazlina; Ang, Gim Wah (2004)
Nowadays, wireless technology has developed into one of the popular topics. Wireless Application Protocol (WAP) is a set of communication protocols, designed to enable wireless devices to access the wealth of information on the Internet. This paper will discuss the objectives, the background study and also explained the proposed system of the WAP based student's information system (WAP SIS) for Faculty of Computer Science and lnformation Technology (FCSIT) The primary objective of the project is to develop a system to facilitate students to navigate or browse the information regardless to geographical location and time by using a WAP enabled handheld device. FCSIT students are capable of retrieving information such as personal file, examination result, course information and announcement and even perform courses registration at their convenience. The system also integrated with management capabilities through administrative features provided in the system. This WAP SIS is hoped to give an easy access for students and also as an alternative to view the FCSIT student's information system at anywhere and anytime.